1994
DOI: 10.1002/pssa.2211420225
|View full text |Cite
|
Sign up to set email alerts
|

Birefringent and piezooptic properties of (MgSiF6) · 6H2O crystals

Abstract: The birefringent and piezooptic properties of (MgSiF,) . 6 H,O crystals are investigated. The secondorder phase transition at = 353 K is observed for the first time. It is shown that the investigated crystals possess properties characteristic of an incommensurate phase in the temperature range 298 to 353 K. The transition temperatures are found to be strongly dependent on the history of the sample. MCCJlenOBaHLI nBynpeJIOMnR€OI4Me II ~L~~O O~T M Y~C K H~ CBOiiCTBa KpHCTannOB (MgSiF,) ' 6 H,O. Bnepmre Ha6nWoAa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Our results agree partially with those reported previously [22] where a study of birefringence δ(Δn i ) showed that pressures σ a and σ c for K 2 ZnCl 4 crystal increase the temperature hysteresis in the commensurate phase for the band a-cross sections whereas they have different effects on its value in the incommensurate phase: σ a decreases it for δ(Δn b ) whereas σ c increases it for δ(Δn b ). Changes of refractive indices in the incommensurate phase.…”
supporting
confidence: 94%
“…Our results agree partially with those reported previously [22] where a study of birefringence δ(Δn i ) showed that pressures σ a and σ c for K 2 ZnCl 4 crystal increase the temperature hysteresis in the commensurate phase for the band a-cross sections whereas they have different effects on its value in the incommensurate phase: σ a decreases it for δ(Δn b ) whereas σ c increases it for δ(Δn b ). Changes of refractive indices in the incommensurate phase.…”
supporting
confidence: 94%
“…After the structurally inhomogeneous phase in MgBF 6 •6H 2 O (B = Si, Ge, Ti) crystals, existing between their rhombohedral paraelastic phase and their monoclinic ferroelastic one, had been discovered by Ziatdinov et al [12][13][14][15], most of the attention of interested researchers [12][13][14][15][17][18][19][20][21][22][23][24][25] was attracted to the nature of this phase (hereafter in this paper called the 'intermediate' phase). For the interpretation of experimental data, various different models of the 'intermediate' phase in these crystals have been suggested: some modifications of the incommensurate structure model [12][13][14][15][17][18][19][20][21][22], a model of static and dynamic disordered structure fragments [23,24] and the domain model [25]. All of these models have been analysed by us previously, with application to MgSiF 6 •6H 2 O [42].…”
Section: In These Compounds Complex A[h 2 O] 2+mentioning
confidence: 99%
“…The physical properties of the (MgGeF 6 ) · 6H 2 O crystals are analogous to the ones in (MgSiF 6 ) · 6H 2 O considered in [9]. The properties of both of them depend from the sample "pre-history".…”
Section: Discussionmentioning
confidence: 83%